Plasma mediated water splitting for hydrogen production - M J Cook; T Nott; W J Trompetter; J Futter; C W Bumby; J V Kennedy (JPhys Energy)
This review explores the potential of enhancing hydrogen production energy efficiency through plasma-mediated water-splitting methods. A variety of plasma types have been explored in the literature for this purpose, including dielectric barrier discharge, microwave, radiofrequency, and gliding arc, with a large range of efficiencies in water splitting. The highest reported efficiencies of up to 80% have been achieved in systems using steam with argon as a carrier gas. The integration of steam in plasma reactors in place of room temperature liquid water contributes a remarkable 20%–50% increase to the overall energy efficiency while the additional energy required in converting water to steam only incurs a 16.4% energy cost to the overall process. Moreover, the addition of argon as a carrier gas in the plasma further enhances overall energy efficiency by an additional 25%–40%, bringing the energy efficiency of these systems up to 80% (based on plasma power). In addition, the use of steam proves advantageous as it prevents significant hydrogen peroxide production (a competing side reaction), and the unreacted steam can be readily condensed or frozen out to separate from the hydrogen and oxygen produced. These enhancements indicate that plasma-mediated water splitting has the potential to achieve similar efficiencies to conventional water electrolysis, with different benefits, paving the way for new applications of hydrogen technology. The disadvantage of plasma systems compared to polymer electrolyte membrane electrolysis is that the hydrogen and oxygen are produced together, however these gases can be readily separated using several technologies. While large-scale plasma systems for water splitting may not currently exist, the potential gains in energy efficiency open avenues for future research and implementation on a larger scale.